Tingkat Perilaku Phubbing Pada Interaksi Mahasiswa Generasi Z - Fauziah, Fauziah; Rihlasyita, Wilda; Amaliati, Siti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Phubbing behavior among generation Z students appears to be concerning where interaction patterns are disrupted with the dominant role of smartphone technology that can undermine active communication. The purpose of this study is to describe the level of phubbing behavior on the interaction of students of generation Z. The method used in this study is a quantitative method with a type of survey research on the presence of phubbing behavior among students of Malang Raya. As for the respondents obtained i.e. 202 respondents dug through the questionnaire with data analysis using normality test with Kolmogorov Smirnov type. As for the results of the research shows that the level of phubbing behavior among generation Z students Malang Raya in the moderate category with the result of the normality test is 0.767 with a significance of 0.599 with a mean of 66.37 or in the moderate category so that the form of interaction failure. educators to provide proper teaching patterns.